Association of Premenstrual Syndrome with Blood Pressure in Young Adult Women - Bertone-Johnson, Elizabeth R. (J Womens Health (Larchmt), 2016)
Objective: The prevalence of hypertension in premenopausal women is increasing. There is substantial need for novel strategies to identify women who would benefit from increased screening and early interventions. Several mechanisms likely contributing to premenstrual syndrome (PMS) are also involved in hypertension, including renin–angiotensin–aldosterone system dysfunction and micronutrient deficiencies. However, it is unknown whether young women with PMS have elevated blood pressure. Materials and Methods: We evaluated the association of blood pressure, PMS, and premenstrual symptoms in a cross-sectional study of 409 young women (mean age 21 years), conducted from 2006 to 2014. Our analysis included 78 cases (19%) who met established criteria for clinically significant PMS and 88 controls (22%) experiencing few symptoms. Blood pressure was measured during the mid-luteal phase. Lifestyle, diet, anthropometry, and other factors were measured by questionnaire and/or direct measurement. Results: After adjustment for smoking, body mass index, and other factors, mean diastolic blood pressure in PMS cases was 72.3 versus 69.1 mm Hg in controls (p = 0.02). Diastolic blood pressure was also significantly higher in women reporting specific symptoms; for example, mean diastolic blood pressure in women reporting moderate or severe premenstrual nausea was 77.7 mm Hg compared with 71.0 mm Hg in women without nausea (p = 0.007). Systolic blood pressure did not vary by PMS status. Conclusions: To our knowledge, this is among the first studies to suggest that diastolic blood pressure is elevated in young adult women experiencing PMS. Prospective studies are needed to determine whether PMS may be a useful sentinel for future hypertension risk in young women.